PRZEDYSKUTUJMY TO NA FORUM – CZYLI O ZDALNYM ROZWIJANIU WYBRANYCH ELEMENTÓW KOMPETENCJI TRANSLACYJNEJ - Tymoszuk, Katarzyna Barbara (Neofilolog, 2021)
The article presents findings of the research into the use of discussion forums in remote learning. This tool was used in a series of academic classes aimed at developing selected elements of translation competence. The paper begins with a discussion of the notion of translation competence and its components, followed by a presentation of didactic objectives formulated for the presented series of classes with full-time teaching in mind, the level of knowledge and skills of the course participants, the degree of realization of the didactic objectives in remote teaching, and conclusions.